PENERAPAN BIAYA KUALITAS DALAM MENINGKATKAN EFISIENSI PRODUKSI PADA PT. TROPICA COCOPRIMA - Ratag, Nilisye Debora; Saerang, David Paul Elia; Mawikere, Lidia (Universitas Sam Ratulangi, 2013)
Competition in the bussines world demanded the company to produce a quality product. In the improvement of quality itself raises the cost called quality cost. The purpose of this study is to know the applying of quality cost in increasing the efficiency production of PT. Tropica Cocoprima. Cost elements quality in general there are four but quality cost at PT. Tropica Cocoprima has three cost elements quality namely; cost of prevention, cost of appraisal, internal failure cost, while the cost of failure is not found on the external company. The biggest quality cost accur in 2011 amounting to Rp. 3.070.883.790,00 or 6,81% from total actual sale. The result show that estimate obtained with the addition cost on cost categories prevention, quality cost decreased amounting to Rp. 2.770.496.414,00 or 2,65% from total actual sale. So, it can be concluded quality cost can improve production efficiency and reduce produce defects.